PENGARUH KARAKTERISTIK INDIVIDU DAN GAYA KEPEMIMPINAN TERHADAP PENINGKATAN KINERJA KARYAWAN DI PT. ROTARYANA ENGINEERING - Sumarsid, Sumarsid; Paryati, Atik Budi (Feb Universitas Dirgantara Marsekal Suryadarma, 2020)
Improving employee performance also affects the performance of the company. One of the factors that influence employee performance is employee characteristics (person characteristic). In addition to human characteristics that are able to influence employee performance, leadership style also contributes to this. Especially PT Rotaryana Engineering employees with a total sample of 60 people. Where leadership is able to bring a company to be more advanced and able to compete. Based on the analysis of the hypothesis test with t test obtained significant value of Individual Characteristics of 0.035 <5% (0.035 <0.05), and the significant value of the variable X2 Leadership Style of 0.000 <5 % (0,000 <0.05), thus Ha (alternative hypothesis) is accepted and Ho (null hypothesis) is rejected. So it can be concluded that the Individual Characteristics and Leadership Style partially have a significant effect on the performance of the employees of PT Rotaryana Engineering.While the results of the analysis of the hypothesis test with the F test obtained a significant value of 0,000 <5%, (0,000 <0.05). Thus Ho is rejected and Ha is accepted, so it can be concluded that: independent variables simultaneously have a significant effect on the dependent variable meaning that simultaneously Individual Characteristics and Leadership Styles have a significant effect on the performance of employees of PT Rotaryana Engineering. Furthermore, the determinant coefficient results obtained that the magnitude of the role or contribution of Individual Characteristics and Leadership Styles significantly influence the performance of employees of PT Rotaryana Engineering is equal to 0.604, thus Individual Characteristics and Leadership Styles have a contribution of 60.4% on the performance of employees of PT Rotaryana Engineering and the rest as much as 39.6% is influenced by other factors that the writer did not examine, for example training, work stress, and cooperative relations between employeesKeywords: Individual Characteristics, Leadership Style and Performance